098 A case of delayed post-hypoxic leukoencephalopathy complicating drug overdose. (29th July 2019) - Fong, Min; Rigby, Nicholas; Pun, Paul; Mitchell, Roger; Schweitzer, Daniel; Swayne, Andrew
Abstract : Introduction: Delayed post-hypoxic leukoencephalopathy (DPHL) is a syndrome characterised by neurological deterioration following a period of recovery after an initial hypoxic event with striking white-matter change on magnetic resonance imaging. We present a case characterised by insidious onset and a fluctuating course of cognitive and neuropsychiatric symptoms. Methods: Single case report. Results: A 61 year old lady, with a background history of previously well managed bipolar affective disorder, was found unresponsive following an intentional overdose of temazepam and tramadol. She was hypotensive, hypoxic and required ventilatory and inotropic support. Following extubation, the patient had residual left-sided weakness and MRI confirmed a right frontal watershed infarction. A three week period of clinical improvement was followed by marked deterioration firstly with fluctuating mood and other neuropsychiatric symptoms which progressed to severe impairment of cognition and alertness. There was generalised slowing on the EEG and the CSF was unremarkable. Repeat neuroimaging undertaken on day 41 of the admission, revealed new symmetric and confluent cerebral white matter changes with high signal on the Diffusion Weighted Images (DWI) and Fluid Attenuated Inversion Recovery (FLAIR) images. The patient was managed with supportive care and sustained a clinically significant recovery (MOCA 26/30), despite ongoing cognitive impairments including working memory and deficits in social cognition including mood instability and disinhibition. Repeat neuroimaging 3 months after initial presentation revealed partial resolution of the white matter changes. Conclusion: A diagnosis of DPHL should be considered in patients with variable mood and cognition following initial improvement after a hypoxic event.